Gaps in tuberculosis knowledge among primary health care physicians in Croatia : epidemiological study - Jurčev Savičević, Anamarija (Array, 2009)
Abstract: High level of tuberculosis (TB) knowledge among physicians is important in order to achieve high case-finding and efficient case-management. Few attempts on how to measure physicians’ TB knowledge and understanding of national TB guidelines in middle-TB incidence countries such as Croatia have been reported. Related surveys were carried out mostly in high or low incidence countries. The aim of this study was to investigate TB knowledge among general practitioners (GPs) and paediatricians in Split and Dalmatian County, Croatia and need for TB education through cross-sectional survey based on anonymous questionnaire sent to all of them and completed by 160 (60.8%) subjects. Although the median percentage of correct responses was not low (70.3%), several areas of concern were revealed. Particularly low knowledge about normal breathing as usual physical chest examination finding in pulmonary TB (43.1%), proper drugs combination in initial phase of treatment (35%), and duration of treatment (61.9%) were found. Need for education in TB control was reported in 87.9% of physicians. TB knowledge score was obtained by the number of correct answers to 14 selected questions and it was 8.18 ± 1.84. Scores according to years of experience, number of treated TB patients and need for education, were not different from each other. Higher score was correlated with paediatricians (p=0.025) and familiarity with existence of National guidelines (p=0.002). This study showed gaps in knowledge among physicians being the cornerstone of TB control in Croatia. Given that the most successful intervention in TB control is early detection and early and appropriate treatment, efforts should be done to increase TB knowledge. Majority of participants were willing to take a part in education. This could be a good starting point for organisation of education activities as one of the approaches to reduce tuberculosis burden in middle incidence countries